Control of Plant Pathogenic Fungi using Organic Solvent Extracts of Leaf Flower and Fruit of Lawsonia inermis L - Jeyaseelan, E.C (International Journal of Pharmaceutical & Biological Archive, 2012)
Control of Plant Pathogenic Fungi using Organic Solvent Extracts of Leaf Flower and Fruit of Lawsonia inermis L